Activity of Some Botanical Extracts Against Fusicladium pongamiae Syd. - Pathak, Hemant; Arjaria, Amita (Indian Forester, 2019)
Five commonly available forest plant species were selected for their antifungal properties. Ethanol extract of leaves of test plants such as Annona squamosa, Albizia lebbek, Lantana camara, Ocimum canum and Gliricidia sepium were tested for inhibition properties against Fusicladium ponagmiae on host plant Pongamia pinnata.